The Future of Waqf: Digital Transformation and Customer Adoption in Islamic Banking - Zaki Fuadi, Nasrul Fahmi; Khabibah, Ani Nur; Irfan, Mohammad (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
This research explores Islamic bank customers' acceptance of the digitalization of cash waqf as a form of waqf transformation in Indonesia. Cash waqf has great potential to support the economic development of the people through social funding sources. By utilizing digital technology, cash waqf transformation aims to increase community participation, expand the scope of waqf, and realize broader social benefits. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model, this research analyzes factors such as performance expectations, business expectations, social influence, and facilitating conditions on customer acceptance. The research results show that all variables have a significant influence, but aspects of religiosity, belief and other factors need to be investigated further. This research contributes to the development of a digitalization system for cash waqf in the sharia banking sector to increase inclusion and effectiveness of waqf.